Aspects of Unity in J. S. Bach's Partitas and Suites : An Analytical Study - Beach, David, 1938- (Book collections on Project MUSE., 2005)
This work provides new insight into the inner workings of Bach's Partitas and Suites, establishing various ways in which the composer linked several movements of a suite to produce a unified effect. Musicians -- listeners, performers, and scholars alike -- have often felt a profound connectedness between various movements in multimovement works by the great composers. But sensing musical unity is one thing; showing it is another. In Aspects of Unity in J. S. Bach's Partitas and Suites, David Beach examines many of the forty-four works by Bach in this genre-for keyboard, orchestra, and solo instruments, including the beloved solo works forviolin and for cello-from this perspective. Through careful attention to motivic and harmonic repetitions at various structural levels, made plain to the eye in numerous annotated musical examples and diagrams, Beach establishes that Bach often did link several movements of a suite in various ways, sometimes by overt but often by more subtle means. Aspects of Unity in J. S. Bach's Partitas and Suites thus provides new insight into the inner workings of these great works. David W. Beach is a renowned music analyst and historian of music theory who recently retired as Dean of the Faculty of Music, University of Toronto. He co-translated Kirnberger's The Art of Musical Strict Composition and edited Aspects of Schenkerian Theory [both for Yale University Press] and is co-editor of Music Theory in Concept and Practice [Eastman Studies in Music, University of Rochester Press].